Successful lactation in Plgrkt-deficient female mice caused by a 1-bp deletion of exon4. Issue 2 (6th May 2022) - Iwaki, Takayuki; Tomonari, Yuki; Umemura, Kazuo
Abstract: Plasminogen (Pg) activation on the cell surface is important for various (patho)physiologic conditions, and Plg-RKT is a cell membrane protein that binds to Pg and promotes its activation. To evaluate the role of Plg-RKT in atherosclerosis, Plgrkt gene in Ldlr −/− /Apobec1 −/− was modified using in vivo CRISPR/Cas9. Synthetic RNA for Plgrkt and Cas9 complex was electroporated into the fertilized eggs in the oviducts. Plgrkt deficient mice were established through a 1-bp deletion, and in this research communication we report their lactational ability. In contrast to Plgrkt −/− mice developed by a conventional method, these newly developed mice did not suffer lactation failure and could maintain their pups until weaning. The major obvious difference between these lines is the area of gene modification. The conventionally developed mouse possesses about 10 kb deletion of Plgrkt, which might relate to the lactation failure. Lactation failure is a lethal phenotype in mammals, and analyses of causative genes are especially important for dairy industries. Further genome-wide analyses with both Plgrkt −/− mice may help to establish causative genes for lactation failure.